INFLUENCE OF BAS ON BLOOD COLLECTION PARAMETERS (Archive of Conferences, 2021)
The use of individual medicinal substances in different directionsactions - anticoagulant, antiplatelet or fibrinolytic in cardiovascular diseases, although it has a positive effect on the conditionsystem of hemostasis, but in case of overdose, it can lead to an undesirable phenomenon.The main function of the hemostasis system is to maintain the integrity of the bloodstream,violation of which can lead to the death of the bobut. In the hemostasis system, they takeparticipation factors of coagulation, anticoagulant (anticoagulant) andfibrinolytic blood systems. The mechanism of hemostasis involves the interaction betweenby the vessel wall, platelets and blood proteins. In this system, balance is very importantbetween the formation of a dense clot, mechanically closing the damage in the vessel,and the preservation of the functions of blood, which it can perform only in liquidcondition. Violations of the hemostasis system - both excessive thrombus formation andbleeding - can lead to serious pathologies